Surface Runoff Management Model of Bandung Regency Through Remote Sensing Analysis - Sugandi, Dede; Ridwana, Riki; Ismail, Arif; Ismail, Jalu Rafli; Sephana, Rafi'i Diva (Jurnal Pendidikan Geografi Gea, 2021)
Flood is caused by surface runoff, therefore controlling the surface runoff is necessary especially on built areas. The aim of this research is to analyze the width, calculating the volume of surface runoff and analyze the model of infiltration wells on built areas in Bandung Regency. The methods implemented in this research is experimental method. This method was carried while analyzing rainfall on built areas samples, which is house building. The land use was analyzed through Landsat 8 imagery in the year of 2019. Rainfall volume was calculated by equation V = h x l. Meanwhile the volume of infiltration well was calculated by equation V = h x k. The result of 2019 Landsat imagery analysis shows that 19.01% of total watersheds in Bandung Regency or as much as 1382.13 km2 is the built areas. The highest rainfall in total of 0.02431 m occurred in October on the area of 197.67 m2 and became a surface runoff of 377,534 m3. In a house building, as built area example, as wide as 90 m3, the amount of 2.19 m3 rainwater needed to be infiltrated. Infiltration well model is a management model on each built areas, so that rainwater on built areas would not be turned into a surface runoff.